2015
DOI: 10.1152/jn.00831.2014
|View full text |Cite
|
Sign up to set email alerts
|

Robust presynaptic serotonin 5-HT1B receptor inhibition of the striatonigral output and its sensitization by chronic fluoxetine treatment

Abstract: The striatonigral projection is a striatal output pathway critical to motor control, cognition, and emotion regulation. Its axon terminals in the substantia nigra pars reticulata (SNr) express a high level of serotonin (5-HT) type 1B receptors (5-HT(1B)Rs), whereas the SNr also receives an intense 5-HT innervation that expresses 5-HT transporters, providing an anatomic substrate for 5-HT and selective 5-HT reuptake inhibitor (SSRI)-based antidepressant treatment to regulate the striatonigral output. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…In addition to ChIs, striatal 5-HT1B heteroreceptor regulates transmission in glutamatergic nerve terminals innervating the nucleus accumbens (36) and in SPNs innervating either the midbrain (37,38) or the pallidum (39), whereas 5-HT1B autoreceptor is found in striatal terminals of serotonergic neurons (40). Interestingly, mice bearing a constitutive deletion of 5-HT1B display aggressive behavior and reduced anxiety relative to WT, but do not display anhedonia (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ChIs, striatal 5-HT1B heteroreceptor regulates transmission in glutamatergic nerve terminals innervating the nucleus accumbens (36) and in SPNs innervating either the midbrain (37,38) or the pallidum (39), whereas 5-HT1B autoreceptor is found in striatal terminals of serotonergic neurons (40). Interestingly, mice bearing a constitutive deletion of 5-HT1B display aggressive behavior and reduced anxiety relative to WT, but do not display anhedonia (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…This would reflect a particular phenomenon that an antidepressant has to overcome the negative tone of 5-HT1B on 5-HT transmission in order to produce a clinical effect. In other words, desensitization and inhibition of 5-HT1B function is mandatory for an antidepressant action [155]. In agreement with this, PET studies have showed that the 5-HT1B binding in brain is reduced in the dorsal brain stem (DBS) after effective treatment of MDD [156].…”
Section: -Ht1b and Depressionmentioning
confidence: 81%
“…Increased adverse side effects and lack of benefits in treating depression in AD were shown in antidepressants particularly sertraline and mirtazapine in a randomized, multicenter, double blind, placebo-controlled trial [236]. We suggest that the refractoriness of SSRIs in AD could be due to SSRI-induced molecular events in AD that might, early, activate or increase expression of 5-HT inhibitory receptors such as 5-HT1B and 5-HT1A instead of the desired desensitization of these receptors [155]. Consequently, activation of these receptors would results in lower intracellular 5-HT levels and subsequent decrease in the release of 5-HT in longer time scales.…”
Section: Modulations Of Sertmentioning
confidence: 88%
“…In this scenario, the relevant 5-HT1B receptors would be expressed by striatonigral (direct pathway) neurons and be situated on their terminals in the substantia nigra to inhibit GABA release from these neurons (Ding et al, 2015; see Castanon et al, 2000, for discussion). Reduced GABA release would be expected to increase (disinhibit) dopamine input to striatal neurons (Castanon et al, 2000).…”
Section: Discussionmentioning
confidence: 99%